Greece's Three-Act Tragedy: A Simple Model of Grexit vs. Staying Afloat inside the Single Currency Area - Yu-Fu Chen; Michael Funke (Center for Economic Studies and ifo Institute (CESifo), 2015)
Against the backdrop of the Greek three-act tragedy, we present a theoretical framework for studying Greece's recent debt and currency crisis. The model is built on two essential blocks: first, erratic macroeconomic policymaking in Greece is described using a stochastic regime-switching model; second, the euro area governments' responses to uncertain macroeconomic policies in Greece are considered. The model's mechanism and assumptions allow either for a Grexit from the euro area or, conversely, the avoidance of Greece's default against its creditors. The model also offers useful guidance to understand key drivers of the long-winded negotiations between the Syiza government and the euro area governments.
Keywords: F34; F45; H63; 330; Greece; currency crisis; euro; financial assistance programmes